Study on adsorption behavior of alkaline protease on poly(ether sulfone) integrated with fish scale hydroxyapatite as self organized in ion exchange membrane - Jamali Sukaimi; Sofiah Hamzah; Nora’aini Ali; Mohd Sabri Mohd Ghazali (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study was performed to investigate the physiochemical effect on the protease adsorption produced by Bacillus sp. using highly specific ion exchange membrane (IExM). Effects of pH solution (adjusted with HCl and NaOH), ionic strength (adjusted by NaCl), and initial concentration on adsorption study were performed by using affinity polyethersulfone (PES) membrane integrated with fish scale hydroxyapatite (FSHAp), FSHAp/PES IExM. At 1.0 M, the maximum adsorption capacity was recorded by 0.229 mg/cm2 in 90 minutes incubation time. The optimum pH was found to be at pH 8 with adsorption capacity of 0.211 mg/cm2 in 90 minutes incubation time. The optimum adsorption capacity with 0.204 mg/cm2 was observed when adsorption study performed with initial concentration at 0.9 mg/ml. Experimental data showed the protease adsorbed higher in alkaline condition compared to acidic solution. Further experiment showed that increase in ionic strength leads to noticeable increase in adsorption capacity which is due to aggregation of enzyme molecules in solution. The adsorption study also showed great adsorption behavior when high initial concentration applied as high number of free enzyme molecule to be adsorbed.